Determinants of Type 2 Diabetes Mellitus among Passive Smokers - Triyaniarta, Adinda Rahma; Martini, Santi; Artanti, Kurnia Dwi; Widati, Sri; Nastiti, Rizma Dwi (UI Scholars Hub, 2022)
Type 2 diabetes mellitus (T2DM) leads to complications of other diseases. The modifiable risk factors for T2DM are overweight, physical activity, hypertension, unhealthy diet, and smoking. This study aimed to analyze determinants of T2DM incidence in passive smokers among various factors. This study was conducted at Hospital X in Surabaya City, East Java Province, Indonesia, from September 2019 to April 2020. The variables were univariate, bivariate, and multivariate. Case samples were T2DM patients and passive smokers, while control samples were non-T2DM patients and passive smokers, with 52 respondents per group, of 104 total respondents. Variables statistically significant related to the incidence of T2DM in passive smokers were age >45 years, level of education (not attaining primary school), lack of physical activity, and hypertension. While, the variables having no relation were sex, occupation, sedentary lifestyles, income, and genetics. The multivariate analysis showed that age was a major factor contributing to the incidence of T2DM in passive smokers at Hospital X Surabaya. In brief, age is the most dominant risk factor for the incidence of T2DM in passive smokers.